Diagnostic accuracy of the clinical indicators to identify central sensitization pain in patients with musculoskeletal pain - Juliana Valentim Bittencourt; Ana Carolina de Melo Magalhães Amaral; Pedro Vidinha Rodrigues; Leticia Amaral Corrêa; Bruno Moreira Silva; Felipe José Jandre Reis; Leandro Alberto Calazans Nogueira (Archives of Physiotherapy, 2021)
Abstract Background The identification of central sensitization (CS) is an important aspect in the management of patients with chronic musculoskeletal pain. Several methods have been developed, including clinical indicators and psychophysical measures. However, whether clinical indicators coincide with the psychophysical test of CS-related sign and symptoms is still unknown. Therefore, the present study aimed to analyze the diagnostic accuracy of the clinical indicators in identifying CS-related sign and symptoms in patients with musculoskeletal pain. Methods One-hundred consecutive patients with musculoskeletal pain were included. Clinical indicators (index method) based on a combination of patient self-report pain characteristics and physical examination were used to identify the phenotype of patients with musculoskeletal pain and the predominance of the CS-related sign and symptoms. Conditioned pain modulation (CPM) was assessed by the Cold Pressor Test (reference standard), which is a psychophysical test used to detect impairment of CPM. Measurements of the diagnostic accuracy were performed. Results Twenty-seven patients presented predominance of CS-related sign and symptoms in the assessment of the clinical indicators, and 20 had impairment of CPM. Clinical indicators showed high accuracy (75.0%; 95% confidence interval = 65.3 to 83.1), high specificity (80.0%; 95% confidence interval = 69.6 to 88.1), high negative predictive value (87.7%; 95% confidence interval = 81.2 to 92.1), and a relevant positive likelihood ratio (2.8, 95% confidence interval = 1.5 to 5.0) when compared to the Cold Pressor Test. Conclusion Clinical indicators demonstrated a valuable tool for detecting the impaired CPM, which is a remarkable feature of the CS-related sign and symptoms. Clinicians are encouraged to use the clinical indicators in the management of patients with musculoskeletal pain.